دور دعم المبادراث الملاولاجيت في الخلليص من ظاهرة البطالت بالجسائر دراست خالت الوكالت الوطنيت لذعم حشغيل الشباب - عبد الرزاق جباري (University of M'Sila, 2024)
الآليات التي ثبىتها سياسة الخشغيل في الجشائز، لدعم 􀗚 هدفد هذه الدراسة إلى الحعزف على مخحلف البرامج و المبادرات المقاولاثية، ودورها في الحقليص من ظاهزة البطالة؛ من خلال إبزاس مساهمة الوكالة الوطىية لدعم جشغيل - .) الشباب كأداة لدعم المبادرات المقاولاثية في ثقليص البطالة خلال الفترة ) 1010 1002 وثوصلد الدراسة إلى عدة هحائج أهمها، أن لجهاس الوكالة الوطىية لدعم جشغيل الشباب باعحباره أحد أهم أجهشة دعم المبادرات المقاولاثية، مساهمة مهمة في ثقليص البطالة؛ كما ثوصلد إلى أن هذا الجهاس يعحبر أهم جهاس لدعم المبادرات المقاولاثية بالجشائز، مقارهة بباقي الآجهشة الآخزى، والتي جعنى بئوشاء المؤسسات المصغزة.
This study aims to identify the various programs and mechanisms adopted by Algeria's employment policy to support entrepreneurial initiatives and their role in reducing unemployment, highlighting the contribution of the National Agency for Youth Employment Support as a tool to promote entrepreneurial initiatives and reduce unemployment during the period 2001-2020. The study reached several findings, the main one being that the National Agency for Youth Employment Support, considered one of the primary support mechanisms for entrepreneurial initiatives, plays an important role in reducing unemployment. It also concluded that this agency is the most significant in Algeria for supporting entrepreneurial initiatives, compared to other mechanisms focused on the creation of micro-enterprises.
Keywords: المقاول; المقاولاتية، أجهزة الدعم، البطالة، سياسة التشغيل، الوكالة الوطنية لدعم تشغيل الشباب; entrepreneur; entrepreneurship; support mechanisms; unemployment; employment policy; National Agency for Youth Employment Support.